احتياجات أولياء أمور أطفال التوحد وعلاقتها ببعض المتغيرات: دراسة ميدانية في مدينة اللاذقية - زيتون، أحمد شوقي (جامعة تشرين, 2017)
هدف البحث إلى تعرف احتياجات أولياء أمور أطفال التوحد لدى أفراد عينة البحث في مدينة اللاذقية، وكذلك تعرف الفروق في احتياجات أولياء أمور أطفال التوحد تبعا لمتغيرات (الجنس، والعمر الزمني للطفل، ودرجة اضطراب التوحد). استخدم المنهج الوصفي، اشتملت عينة البحث على (182) ولي أمر، في الفصل الأول من العام الدراسي 2016- 2017، كما استخدم استبانة احتياجات أولياء، والتي تألفت من (40) بندا، التي تكون من أربعة مجالات. واستخدم الأساليب الإحصائية التالية: المتوسطات الحسابية، واختبار (t)، وتحليل التباين الأحادي (ANOVA). وللحكم على صدق الاستبانة عرضت على مجموعة مؤلفة من (7) محكمين مختصين، وتم التأكد من ثباتها بتطبيقها على عينة استطلاعية شملت (22) ولي أمر من خلال حساب معامل ألفا كرونباخ (Cronbach- Alpha)، والذي بلغ (0.828). توصلت النتائج إلى أن درجة احتياجات أولياء أمور أطفال التوحد لدى أفراد عينة البحث في مدينة اللاذقية جاءت مرتفعة، وقد وجدت فروق ذات دلالة إحصائية بين درجات أفراد عينة البحث حول درجة تقديرهم لاحتياجات أطفالهم التوحدين تبعا لمتغير الجنس ولم توجد فروق ذات دلالة إحصائية تبعا لمتغيري (العمر الزمني للطفل، ودرجة اضطراب التوحد). قدم البحث توصيات عدة منها زيادة المراكز المتخصصة التي ترعى الأبناء ذوي اضطراب التوحد في محافظة اللاذقية.
This research aimed to know the needs of parents’ of children with autism spectrum disorder Lattakia city, also aimed to examine the differences in needs of parents of children with autism spectrum disorder to the variables (sex, age and degree of disability). the research used descriptive analytical method, the sample included (182) parents in the academic year 2016/2017. the research used needs of parents’ of children questionnaire consisted of (40) items, distributed to four areas. the following statistical methods were used: means, t – test, Cronbach Alpha, And One Way ANOVA. Validity of the questionnaire was established though a jury of (7) of the teaching staff at Damascus and Tishreen Universities. Pilot sample consisted of (22) Parents. Reliability was established by Cronbach – Alpha Reliability at least (0.828). The final results showed that the degree of the needs of parents of children with autism spectrum disorder were higher rated for the sample research. in fact, there were significant differences about the needs of parents of children with autism spectrum disorder related to the sex, but there no were significant differences related to the (age and degree of disability). The research had some suggestions about increase the specially centers which to take care of the children with autism spectrum disorder in Lattakia city.
Keywords: التربية الخاصة -- أطفال التوحد -- التنشئة الأسرية -- سوريا